ETIKA DALAM PENANGANAN EKSPLAN KULTUR JARINGAN PISANG BARANGAN (Musa acuminata L.) YANG TERKONTAMINASI: PERSPEKTIF KEAMANAN PANGAN DAN KESEHATAN MASYARAKAT - Diana Citra, Umi; Nabila Ma’rufi Ridwan, Radhika; Indriani, Pramita; Haniyah, Ummu (Jurnal Biogenerasi, 2024)
Barangan banana (Musa acuminata L.) is one of the banana varieties that is highly valued commercially and has potential for further development. Microbial contamination such as fungi and bacteria is often the main problem in in-vitro propagation of banana seeds. The explant itself, equipment, work environment, and non-sterile culture media can cause contamination. Colletotrichum sp., Aspergillus sp., Penicillium sp., Rhizoctonia sp., and gram-positive bacteria are several types of contaminants that are often found in Barangan banana explants. There is a possibility of mycotoxin production and the spread of disease because this contamination can endanger food safety and public health. Handling of contaminated explants must be done in an environmentally friendly and safe manner for workers. In addition, ethics, occupational safety, food safety, and ethical principles in agricultural biotechnology research must be considered when using decontamination agents or other sterilization methods. To maintain food safety and public health, strict procedures are required.